The Effectiveness of Inside-Outside Circle in Teaching Speaking Skill - Sajidar, Hana; Salam, Urai; Husin, Syarif (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aimed to determine the effectiveness of the Inside-Outside Circle technique in teaching speaking skills. A pre-experimental design was used as the research method. The sample was selected through cluster random sampling, consisting of 24 students from class VIII E at SMP Negeri 11 Pontianak. Based on the findings, the t-test result was 8.43, which was higher than the t-table value of 2.064 at a significance level of 0.05 with a degree of freedom (df) of 23 (N-1 = 24-1). The effect size was calculated at 1.68, indicating a strong effect. Consequently, the Null Hypothesis (H?) was rejected, and the Alternative Hypothesis (H?) was accepted. In conclusion, implementing the Inside-Outside Circle technique is highly effective in enhancing the speaking skills of eighth-grade students at SMP Negeri 11 Pontianak in the 2024/2025 academic year.